INTEGRASI RUANG PULAU KARAMPUANG DI KABUPATEN MAMUJU - Cahyani, Cahyani -; Permata, Nike Dyah; Mustakima, Dui Buana; Nugroho, Isti; Hikmah, Nurul (JAMBURA Journal of Architecture, 2025)
Karampuang Island is one of the leading marine tourism destinations in Mamuju Regency, possessing significant potential for sustainable tourism development. However, limited road infrastructure and transportation accessibility pose major challenges in spatial integration between Karampuang Island and Mamuju City. This study aims to analyze road space integration in supporting connectivity and sustainable tourism development on Karampuang Island. The research employs a qualitative descriptive approach with spatial planning analysis, transportation infrastructure assessment, and coastal area management policy review. The findings indicate that connectivity between Karampuang Island and Mamuju City remains limited due to inadequate transportation routes and a lack of supporting infrastructure facilities. Enhancing the quality and quantity of land and sea transportation routes, sustainable spatial planning, and integrative policies in coastal area management are essential to improving regional connectivity. Furthermore, the development of environmentally friendly road infrastructure tailored to tourist needs can support the advancement of Karampuang Island as a marine tourism destination that is better integrated with Mamuju City. Thus, optimizing road space integration not only improves accessibility but also contributes to local economic growth and coastal ecosystem sustainability.